Evaluating Large Patch-Tolerant and Cold Hardy Zoysiagrass Germplasm in the Transition Zone - Mingying Xiang; Jack Fry; Megan Kennelly (Kansas Agricultural Experiment Station Research Reports, 2019)
More than 2,800 zoysiagrass progeny, all having a single parent in common that exhibited tolerance to large patch, were evaluated in several transition zone states for quality characteristics and large patch tolerance. From these evaluations conducted over several years, 10 progeny have been identified for further evaluation that have good quality and large patch tolerance that is superior to Meyer zoysiagrass.
Keywords: disease; turfgrass; large patch